[Zwissler, Laurel. Religious, feminist, activist: cosmologies of interconnection] - Žáková, Michaela (Religio, 2019)
Zwissler, Laurel. Religious, feminist, activist : cosmologies of interconnection. Lincoln : University of Nebraska Press, 2018. 324 s. ISBN 978-0-8032-8570-5.